The use of computerised accounting systems among accountants on small and micro businesses in Xi'an, Shaan Xi of China - Zhang, Lanlan (2017)
The main purpose of this study is to examine the relationship between the perceived ease of use, perceived usefulness and usage of Computerized Accounting System (CAS) among accountants in small and micro businesses in Xi’an, Shaan Xi of China. This study uses the quantitative method for data analysis. Data were collected using a set of questionnaires distributed to a sample of 400 accountants, 221 of the questionnaire were returned and only 201 were used for further analysis. The results showed a positive relationship between perceived ease of use, perceived usefulness and the use of CAS. About the current usage state of CAS in China, there were about 73.6 % of businesses already implemented CAS in Xi’an Shaan Xi of China. U8 as the most popular type of accounting software, has about 32.8 % of the respondents. The recommendation for this research can be improved by conducting the other factors that have effect on the adoption of CAS. A larger sample should also be covered not just focus on the selected city of China. The data from this research is collected from the online survey. Another approach should also be considered for data collection. Through information provided in this research, accountants, business owners, government, software provider and other related parties could acquire a better understanding of the benefits of CAS. Most of the previous studies were undertaken outside of China such as United States, Kenya, Nigeria, and Malaysia. This study try to form the perspective of the small and micro businesses on the usage and the implementation of CAS especially in Xi’an, Shaan Xi of China to encourage them to use the accounting software.